Happiness and Work Productivity among Civil Servants in a 3T Region: A Correlational Study in West Halmahera Indonesia - Christinata Angeline Tjida; Susana Prapunoto (Universitas PGRI Yogyakarta, 2026)
Research on the relation between happiness and work productivity has predominantly been conducted in urban private-sector settings, whereas studies focusing on civil servants in underdeveloped, frontier, and outermost regions (3T areas) such as West Halmahera remain limited. This study aims to examine the relationship between happiness and work productivity among administrative civil servants at Office X in West Halmahera. A quantitative approach with a cross-sectional correlational design was employed, involving 97 administrative employees selected through probability sampling based on the Krejcie and Morgan sample size table from a total population of 130 employees. Data were collected using the Oxford Happiness Questionnaire (OHQ) and the Individual Work Performance Questionnaire (IWPQ), and analyzed using Pearson’s product–moment correlation. The findings revealed a very strong and statistically significant positive relation between happiness and work productivity (r = 0.803; p < 0.001). In addition, 100% of respondents were categorized as having high levels of happiness, and 99% demonstrated high levels of work productivity. These findings contribute to the development of industrial and organizational psychology literature within the public sector, particularly in 3T regions, and provide practical implications for local governments in designing strategies to enhance employee happiness and productivity in public service delivery. Keywords: civil servants, happiness, public service, work productivity, 3T regions